Assessment of Hepatoprotective and Antioxidant Effect of Acioa barteri Extract (ABE) in Alloxan-Induced Diabetic Rats - Uroko, Robert Ikechukwu; Ogbonna, Henry Nnaemeka; Aguwamba, Chinedu; Nweje-Anyalowu, Paul Chukwuemeka; Umezurike, Benedict Chidozie (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
This study aimed to investigate the effects of Acioa barteri extract (ABE) on hepatocellular enzyme activity, hepatic function, and antioxidant stress indices in diabetic rats induced with alloxan. The antidiabetic effect of ABE was evaluated in six experimental groups: normal controls, diabetics untreated, diabetics treated with 200mg/kg, 400mg/kg, or 800 mg/kg ABE, and diabetics treated with 3 mg/kg Glibenclamide. ABE was orally administered to induce diabetes, and alloxan-monohydrate was intraperitoneally administered. Diabetic untreated rats exhibited significantly elevated levels of alkaline phosphatase, aspartate, and alanine transaminase activities, as well as higher concentrations of total bilirubin, conjugated bilirubin, and malondialdehyde. They also showed decreased levels of total protein, albumin, globulin, and protein-bound iodine, along with reduced antioxidant enzyme activity. In contrast, diabetic rats administered ABE demonstrated reduced hepatocellular enzyme activity and improved hepatic function. These rats exhibited increased levels of total protein, globulin, and albumin, as well as higher levels of glutathione, superoxide dismutase, glutathione peroxidase, and catalase activities, compared to diabetic untreated rats. The findings suggest that ABE may help prevent oxidative stress and improve hepatic functions in diabetic rats. ABE treatment led to decreased hepatocellular enzyme activity and improved hepatic function, along with increased antioxidant enzyme activities. These results highlight the potential of ABE as a therapeutic option for diabetes-induced liver dysfunction. Further research is warranted to explore its mechanisms of action and potential clinical applications.